Oxytocin facilitates human touch-induced play behavior in rats - Hayashi, Himeka; Tateishi, Sayaka; Inutsuka, Ayumu; Maejima, Sho; Hagiwara, Daisuke; Sakuma, Yasuo; Onaka, Tatsushi; Grinevich, Valéry; Sakamoto, Hirotaka (Current biology, 2025)
Pleasant touch sensations play a fundamental role in social bonding, yet the neural mechanisms underlying affinity-like behaviors remain poorly understood. Here, we demonstrate that juvenile-adolescent rats, which naturally engage in social play with peers characterized by rough-and-tumble interactions and 50 kHz ultrasonic vocalizations indicating pleasant sensations, develop a strong affinity for human hands through similar playful contact achieved by repeated tickling with human hands. Using this rat with tickling-induced high affinity for human hands, we discovered that repeated tickling mimicking rough-and-tumble play led to increased oxytocin receptor (OTR) expression in the ventrolateral part of the ventromedial hypothalamus (VMHvl). Inhibition of oxytocin signaling in the VMHvl reduced affinity-like behaviors from rats to human hands. These findings suggest that OTR neurons in VMHvl play an important role in the increase in affinity for human hands induced by pleasant touch sensation with human touch-induced play behavior. Based on retrograde and anterograde tracing studies examining the supraoptic nucleus (SON) and the paraventricular nucleus (PVN) as primary sources of oxytocin, we demonstrate that a subset of oxytocin fibers in the VMHvl originate from the SON, suggesting that affinity-like behavior from rats to human hands may be controlled by oxytocin signaling from magnocellular neurons. Together, this work advances our understanding of how oxytocin shapes social behavior and may inform the development of therapeutic strategies to promote positive social interactions.
Online verfügbar: 4. Juni 2025, Artikelversion: 23. Juni 2025
Gesehen am 02.12.2025